1980
DOI: 10.1152/ajpheart.1980.238.3.h360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemorrhage on blood flow to marrow and osseous tissue in conscious rabbits

Abstract: The effect of hemorrhage on blood flow to marrow and osseous tissue was determined in conscious rabbits by injecting radioactive microspheres (15 micron diam) at three time intervals: pretreatment control; 15 min after nonfatal hemorrhage (20 ml/kg body wt), and 16 h posthemorrhage. Cardiac output (CO), blood pressure, heart rate, resistance, arterial PCO2, PO2, and pH, and hematocrit were measured at each time interval. Tissues analyzed included heart, spleen, kidney, and femur with marrow and osseous tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…It was reported that changes in BBF was dependent on CBF changes which were proportional to cardiac output (31). Results of the present study agree with that study because BBF increases were proportional to CBF increases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was reported that changes in BBF was dependent on CBF changes which were proportional to cardiac output (31). Results of the present study agree with that study because BBF increases were proportional to CBF increases.…”
Section: Discussionsupporting
confidence: 92%
“…Although mechanisms for the redistribution is unclear, it is possible that vascular responses to carbon dioxide itself and secondary sympathetic acceleration or inhibition may be different among various tissues such as bone marrow, 13 skeletal muscles, periosteum, and mucosal membrane (13,(31)(32)(33). It is reported that distributive ratio of adrenergic alpha and beta receptors are different between skeletal muscles and skin / mucosal membrane (34).…”
Section: Discussionmentioning
confidence: 99%
“…CO was thetized operated animals. The marrow flow of 10.7% of CO oportion of blood going to the marrow was similar to that described in other reports (7,15 7) row iron uptake was increased only three times. Nevertheless, marrow iron flow had increased more than fivefold, due to the increase in plasma iron concentration, in plasmatocrit, and in marrow blood flow.…”
Section: Resultssupporting
confidence: 89%
“…This type of mapping has mainly been performed by adapting whole-bone methods such as radioactive microspheres, while hydrogen washout may be better suited. [43][44][45][46] Criteria for an ideal blood flow measurement method were outlined by Jacobson 47 : providing accurate and reproducible quantitative data with the capacity to distinguish between total and intraorgan distribution of blood flow, sensitive to rapid changes, capable of continuous monitoring, requiring minimal disturbance of the subject, independent of other measurements, safe, inexpensive, and easy to perform. The microsphere method is hampered by the limited number of measurements possible during each experiment, the necessary precautions associated with radioactive material, and the necessity for removal of the organ for measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular consideration are the many parameters that need to be accurately accounted for: sufficient mixing in the central circulation, good first pass extraction, no separation from the blood, no measurement possible in the second of two capillary beds in series, no obstruction of arterioles, tracer leakage from particle, homogenous particle size, and label intensity. 48 Despite these limitations, it has been used under many different experimental circumstances to measure regional bone blood flow 2,33,37,39,40,43,45, and has been used to validate new blood flow methods in bone such as noble gas washout 34 and laser Doppler flowmetry. 70 The hydrogen washout method of regional blood flow measurement was developed by the Norwegian physiologist Aukland and colleagues 38 and first applied to bone tissue by Whiteside et al 6 in the rabbit; he assumed that his measurements were accurate because they were similar to those reported by other methods.…”
Section: Discussionmentioning
confidence: 99%